2021
DOI: 10.3390/ijms22052597
|View full text |Cite
|
Sign up to set email alerts
|

Surface Activation of Titanium Dental Implants by Using UVC-LED Irradiation

Abstract: Organic contaminants significantly limit the bioactivity of titanium implants, resulting in the degradation known as the ageing of titanium. To reactivate the surfaces, they can be photofunctionalized, i.e., irradiated with C-range ultraviolet (UVC) light. This descriptive in vitro study compares the effectiveness of novel light-emitting diode (LED) technology to remove contaminant hydrocarbons from three different commercially available titanium dental implants: THD, TiUnite, and SLA. The surface topography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…For this reason, UVC pretreatment was applied in this study to optimize the bioactivity and antimicrobial activity of different Ti surfaces. After UVC pretreatment, both smooth and nano-Ti surfaces achieved a static WCA at 0° ( Table 2 ) as evidence of a super-hydrophilic transition ( Figure 1 G,H) without significant changes in surface topography or roughness, which was consistent with the previous research [ 33 ]. This phenomenon was explained by the removal of carbohydrate contaminants and the production of hydrophilic chemicals [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, UVC pretreatment was applied in this study to optimize the bioactivity and antimicrobial activity of different Ti surfaces. After UVC pretreatment, both smooth and nano-Ti surfaces achieved a static WCA at 0° ( Table 2 ) as evidence of a super-hydrophilic transition ( Figure 1 G,H) without significant changes in surface topography or roughness, which was consistent with the previous research [ 33 ]. This phenomenon was explained by the removal of carbohydrate contaminants and the production of hydrophilic chemicals [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have confirmed that the tendency of organic components adsorption and decrease in hydrophilicity also occurred on surfaces of titanium alloys during biological aging [11,13]. Additionally, it has been demonstrated that the effect of UV-irradiation could regenerate the biological properties of titanium alloys as well [56,57]. Given that the alloy elements could contribute to enhancing photocatalytic performance of titanium alloys [58], the mechanism of improving biological performance under UV-irradiation could be different from that of pure titanium and remains to be further studied.…”
Section: Discussionmentioning
confidence: 77%
“…Several papers [112,113] have underlined the different instrumentation and methodology advances that have enhanced the ability to study organic and biological systems through XPS spectroscopy. Among the biological systems and biomaterials which can be investigated through XPS spectroscopy, we can quote bacteria [114,115], Human cells [116,117], dental implants [118][119][120], intraocular lens [121,122] or physiological as well as pathological calcifications such as (not only human ones) [123][124][125], teeth [126][127][128], vascular calcifications [13,129] or kidney stones [130].…”
Section: Selected Examples Related To Medicinementioning
confidence: 99%